Порівняльно-морфологічна характеристика будови квітки видів роду Coelogyne Lindl. (Orchidaceae Juss.) з колекції Національного ботанічного саду ім. М.М. Гришка НАН України - Kovalska, L.A.; Gyrenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The inflorescence development patterns as well as morphological structure of the flowers of 9 Coelogyne Lindl. (Orchidaceae Juss.) species from the M.M. Gryshko National Botanical Garden of the NAS of Ukraine collection – C. brachyptera Rchb. f., C. dichroanthа Gagnep., C. fimbriata Lindl., C. flaccida Lindl., C. huettneriana Rchb. f., C. nitida (Wall. ex D. Don) Lindl., C. ovalis Lindl., C. speciosa Lindl., C. tomentosa Lindl. are studied.